2016
DOI: 10.12659/msm.900688
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA (LncRNA) Urothelial Carcinoma Associated 1 (UCA1) Increases Multi-Drug Resistance of Gastric Cancer via Downregulating miR-27b

Abstract: BackgroundIn this study, we aimed to investigate the association between UCA1 and miR-27b in gastric cancer and further study their involvement in multi-drug resistance (MDR) of gastric cancer.Material/MethodsThe microarray data of dysregulated lncRNAs in gastric cancer tissues was retrieved in the GEO dataset. QRT-PCR analysis was performed to assess UCA1 expression based on 28 paired cancerous and peritumoral normal tissues. The human gastric cancer cell line SGC-7901, and SGC-7901 derived Adriamycin (doxoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…24,25 One study reported that UCA1 silencing impaired lung cancer cell proliferation and colony formation by regulation of miR-193a-3p. 27 Further, Fang et al 28 found that UCA1 could increase the multidrug resistance of GC through downregulation of miR-27b. 27 Further, Fang et al 28 found that UCA1 could increase the multidrug resistance of GC through downregulation of miR-27b.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 One study reported that UCA1 silencing impaired lung cancer cell proliferation and colony formation by regulation of miR-193a-3p. 27 Further, Fang et al 28 found that UCA1 could increase the multidrug resistance of GC through downregulation of miR-27b. 27 Further, Fang et al 28 found that UCA1 could increase the multidrug resistance of GC through downregulation of miR-27b.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, UCA1 could sponge the miR-590-3p targeting cyclic adenosine monophosphate response element-binding protein 1 (CREB1), and knockdown of CREB1 inhibits the growth of human GC in vitro and in vivo [67,68]. Moreover, UCA1 increased multi-drug resistance of GC by downregulating miR-27b [69]. Colon cancer is one of the most common cancers in the world, characterized by unlimited proliferation and high metastasis [70].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…It has been experimentally validated that lncRNAs are involved in the etiology and pathogenesis of various cancers, including BLCA [13][14][15][16][17][18][19][20]. The recent advances in high-throughput data technologies, including RNAsequencing and microarrays, has guided the identification of lncRNAs for prospective clinical application in BLCA [12,[21][22][23]. However, most previous studies focused on the clinical value of individual lncRNAs, which has limited potential for future clinical application.…”
Section: Introductionmentioning
confidence: 99%